Recollections of the Private Life of Napoleon Volume 04 - Wairy, Louis Constant, 1778-1845; Clark, Walter, 1846-1924 (Salt Lake City, UT : Project Gutenberg, 2002)
"Recollections of the Private Life of Napoleon Volume 04" by Louis Constant Wairy is a historical account written in the late 19th century. This volume delves into the personal experiences and observations of Constant, who served as the premier valet de chambre to Napoleon Bonaparte. The narrative likely provides an intimate look at the life and character of Napoleon, interspersed with anecdotes about the court and those around him, including his relationships with family and political figures. At the start of the text, Wairy reflects on his marriage and its significance, linking it to the broader context of his life under Napoleon s reign. He recounts how his wife s family became intertwined with the Bonaparte family, illustrating the patronage and support provided by Madame Bonaparte, who became the Empress Josephine. The opening chapters detail the interactions of the Charvet family with the Bonapartes, integrating personal stories of affection and kindness amid the backdrop of historical events, including the organizational aspects of the Emperor s household and the significant role of Empress Josephine in both political and familial matters. Through a mix of personal reminiscences and historical detailing, Wairy sets the stage for a rich exploration of life at the imperial court. (This is an automatically generated summary.)
Uniform title: Mémoires de Constant. English
Release date is 2002-12-01
This etext was produced by David Widger
Keywords: Napoleon I, Emperor of the French, 1769-1821; Napoleon I, Emperor of the French, 1769-1821 -- Contemporaries; Wairy, Louis Constant, 1778-1845; Napoleon I, Emperor of the French, 1769-1821 -- Relations with valets; Valets -- France -- Biography